2017
DOI: 10.1152/japplphysiol.00344.2017
|View full text |Cite
|
Sign up to set email alerts
|

Is normobaric hypoxia an effective treatment for sustaining previously acquired altitude acclimatization?

Abstract: This study examined whether normobaric hypoxia (NH) treatment is more efficacious for sustaining high-altitude (HA) acclimatization-induced improvements in ventilatory and hematologic responses, acute mountain sickness (AMS), and cognitive function during reintroduction to altitude (RA) than no treatment at all. Seventeen sea-level (SL) residents (age = 23 ± 6 yr; means ± SE) completed in the following order: ) 4 days of SL testing;) 12 days of HA acclimatization at 4,300 m; ) 12 days at SL post-HA acclimatiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…As the differing timelines suggest (Banderet et al, 2002), AMS development and cognitive performance decrements do not seem to be related in the current study. While some have found correlations between AMS and cognitive performance decrements (Forster, 1985; Shukitt‐Hale et al, 1991), others have not (Abraini et al, 1998; Beidleman et al, 2017; Kramer et al, 1993) and it is generally believed they are not directly related (Shukitt‐Hale et al, 1991; Virues‐Ortega et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As the differing timelines suggest (Banderet et al, 2002), AMS development and cognitive performance decrements do not seem to be related in the current study. While some have found correlations between AMS and cognitive performance decrements (Forster, 1985; Shukitt‐Hale et al, 1991), others have not (Abraini et al, 1998; Beidleman et al, 2017; Kramer et al, 1993) and it is generally believed they are not directly related (Shukitt‐Hale et al, 1991; Virues‐Ortega et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Upon re-exposure to a simulated altitude of 4300 m (hypobaric chamber) after a 12-day stay at sea level, only 17% developed AMS, indicating that a large acclimatization effect was retained. Interestingly, normobaric hypoxia exposure (3 h per day during the sea level stay) did not further reduce AMS development [9]. These findings, however, rather demonstrate a prolonged (12 days) effectiveness of prior acclimatization rather than corroborating ineffectiveness of normobaric hypoxia for pre-acclimatization.…”
Section: How Long Are (Pre-)acclimatization Effects Retained?mentioning
confidence: 60%
“…In another study, out of 17 young sea level residents, 88% developed AMS (using the LLQ criteria) during the initial high-altitude exposure (4300 m), which declined to 0% during the 12-day acclimatization period [9]. Upon re-exposure to a simulated altitude of 4300 m (hypobaric chamber) after a 12-day stay at sea level, only 17% developed AMS, indicating that a large acclimatization effect was retained.…”
Section: How Long Are (Pre-)acclimatization Effects Retained?mentioning
confidence: 97%
“…Others have reported that sleep acclimatization occurs at altitudes above 4000 m (Fulco et al, 2011;Nussbaumer-Ochsner et al, 2012;Reite et al, 1975) but is questionable at lower altitudes (Fischer et al, 2004;Orr et al, 2018;Tseng et al, 2015). In addition, a decrease in AMS prevalence and severity over 4 days of exposure to 4300 m has been shown repeatedly by others (Beidleman et al, 2017;Fulco et al, 2011).…”
Section: Discussionmentioning
confidence: 93%